P-BN10 Seasonal Variation of Presentation of Perforated Peptic Ulcer Disease: An Overview of Patient Demographics, Management and Outcomes in Northern Ireland. (16th December 2021) - Yawar, Bakhat; Marzouk, Ahmed; Ali, Heba; Diab, Alsarah; Abdulrahman, Hassan; Asim, Asim; McCann, Laura; Fleville, Samara; Asim, Ayeisha; Bahli, Zahid; Abousamra, Mohammad; Ghorab, Tamer
Abstract: Background: Perforated peptic ulcer disease is one of the most common causes of acute peritonitis. It carries significant mortality and morbidity. Several previous studies have reported a seasonal variation in presentation of patients with perforated ulcers. Here we present this study from a Northern Irish perspective on perforated peptic ulcers. Methods: A retrospective cohort study was conducted on perforated peptic ulcer patients who presented to Altnagelvin Area Hospital emergency department between 2015 to 2020. Data on patient demographics, clinical presentation, investigations, management and outcomes were collected. Primary outcome was to investigate if seasonality was associated with incidence of perforated peptic ulcers. Follow-up data was also collected. Seasons were defined as per UK Met Office. Results: Results: A total of 50 patients presented with perforated PUD. Male:female ratio was approximately 3:2. Peaks were noted in spring and winter. April was the most common month for presentation followed by December. Smoking was the most common risk factor followed by alcohol abuse. 14 patients (28%) were either very frail or had contained perforations and were conservatively managed. 3 deaths were noted (6%). 13 patients (26%) required ICU admission at some stage in their management. Conclusions: Slight seasonal variation was noted in presentation of perforated peptic ulcers in our study with more common incidence in winter and spring months. The month of April was noted to have the peak incidence of the disease in our study.